Stomach and duodenal ulcer as a cause of death in patients with cancer: a cohort study - Ramez M. Odat; Muhammad Idrees; Mohammed Dheyaa Marsool Marsool; Shahed Mamoun Oglat; Salma Omar Tbayshat; Zaid Ibrahim Adnan; Yousef Adeeb Alkhateeb; Ali O. Aldamen; Hritvik Jain; Dang Nguyen; Hamdah Hanifa (International Journal of Emergency Medicine)
Abstract Introduction Non-cancer deaths are now becoming a significant threat to the health of cancer patients. Death from stomach and duodenal ulcer is linked to cancer due to the side effects of treatment and its pathogenesis. However, guidelines for identifying cancer patients at the highest risk of death from stomach and duodenal ulcer remain unclear. Methods Data of all patients diagnosed with cancer between 2000 and 2021 were obtained from the Surveillance, Epidemiology, and End Results (SEER) database. Data regarding the causes of death and clinicopathological features such as sex, age, race, marital status, SEER stage, and treatment procedures were extracted. We calculated standardized mortality ratios (SMRs) using the SEER*Stat software V8.4.3. Results Of the 6,891,191 cancer patients, 2,318 died of stomach and duodenal ulcer, a rate higher than that in the general population (SMR = 1.58, 95% CI [1.52–1.65]). Stomach and duodenal ulcer-related deaths decreased over time from 870 deaths between 2000 and 2004 to 294 deaths between 2015 and 2019. Among the 2,318 stomach and duodenal ulcer deaths, the highest numbers were observed in patients with prostate cancer (n = 389, 16.8%), and lung and bronchus cancer (n = 255, 11%). Patients with liver and intrahepatic bile duct cancers (SMR = 10.53, 95% CI [8.3-13.18]), and pancreatic cancer (SMR = 6.84, 95% CI [5.11–8.97]) had a significantly higher rate of death from stomach and duodenal ulcer than the general population. Conclusion Our study revealed a significantly higher risk of stomach and duodenal ulcer mortality among patients with cancer in the United States, underscoring the critical need for integrated care strategies that address both cancer and ulcer-related complications. To reduce ulcer-related mortality, we recommend the implementation of targeted prevention protocols, including routine gastrointestinal screenings for high-risk cancer patients, proactive management of ulcer risk factors, and collaboration between oncology, gastroenterology, and surgical teams. Graphical abstract